Reappraisal of Total Pancreatectomy in 45 Patients With Pancreatic Ductal Adenocarcinoma in the Modern Era Using Matched-Pairs Analysis: Multicenter Study Group of Pancreatobiliary Surgery in Japan. Issue 7 (August 2016) - Satoi, Sohei; Murakami, Yoshiaki; Motoi, Fuyuhiko; Sho, Masayuki; Matsumoto, Ippei; Uemura, Kenichiro; Kawai, Manabu; Kurata, Masanao; Yanagimoto, Hiroaki; Yamamoto, Tomohisa; Mizuma, Masamichi; Unno, Michiaki; et al.
Abstract : Objective: The aim of this study was to reappraise the clinical role of total pancreatectomy with curative intent in patients with pancreatic ductal adenocarcinoma (PDAC). Methods: In 2001 to 2011 database from 7 institutions in Japan, 45 (3.1%) of 1451 patients with PDAC underwent total pancreatectomy (TP group), and 885 patients underwent pancreaticoduodenectomy (PD group). A matched-pairs group consisted of 45 patients matched for age, sex, year, resectability status, and neoadjuvant therapy (matched-PD group). Clinicopathological data, overall survival, and disease-free survival were compared between groups. Results: Clinical features of the TP group revealed higher-stage disease, greater surgical stress, a higher frequency of lymph node metastasis, and a lower adjuvant chemotherapy completion rate compared with the PD group ( P < 0.05). Overall survival and disease-free survival in the TP group were significantly worse than those in the PD group ( P < 0.05). Multivariate analysis revealed resectability status, neoadjuvant therapy, blood transfusion, lymph node metastasis, and adjuvant therapy to be significant prognostic factors. No differences in mortality and morbidity rates were observed between the 2 groups. A matched-pairs analysis revealed similar surgical outcomes and overall survival. Conclusions: The surgical outcome of total pancreatectomy for patients with PDAC is acceptable. When margin-negative resection is expected, total pancreatectomy should not be abandoned in the modern era.